Modelling participation, resistance to change, and organisational citizenship behaviour: A South African case - P. Msweli-Mbanga; N. Potwana (South African Journal of Business Management, 2006)
The purpose of this paper is two-fold. First, to establish the extent to which employees from State Owned Enterprises are provided with information and opportunities to participate in change efforts in their organisations. Secondly, to verify the relationship between access to participation, willingness to participation, resistance to change and organisational citizenship behaviour, by testing a model that links these four constructs together. While the results of this study support the hypothesis that access to participation is positively linked to willingness to participate, we found that personnel from the State Owned Enterprises are not provided adequate access to participate in change efforts. The hypothesis that willingness to participate in change efforts in organisations has a higher propensity to reduce resistance to change was also supported. The implications of these findings are discussed and avenues for further research offered.
Keywords: 650